Management of Complicated Wounds of the Extremities with Scapular Fascial Free Flaps - Datiashvili, Ramazi O.; Yueh, Janet H. (Journal of Reconstructive Microsurgery, 2012)
Management of complicated open wounds of the extremities represents a reconstructive challenge. The goal of reconstruction is to provide coverage of exposed vital structures with well-vascularized tissues for optimal restoration of its form and function. We present our experience with the use of scapular fascial free flaps in the reconstruction of complicated open wounds of the extremities. During the period 2001 to 2009, a total of 12 reconstructions utilizing scapular fascial free flaps were performed: nine for upper extremity wounds and three for lower extremity wounds. Two flaps failed: in one case due to intractable vasospasm, in the other case due to lack of adequate recipient vessels. In the ten successful cases, good functional and aesthetic outcomes were achieved. Based on our experience, we conclude that the scapular fascial free flap, although technically demanding, could be considered as the flap of choice for reconstruction of complicated open wounds of the extremities; it provides ample thin and well vascularized soft tissue coverage with restoration of function and a natural contour of the extremity.
Keywords: scapular fascial free flap; complicated wounds; extremity reconstruction; hand reconstruction